Analisis Pengaruh Pelayanan Pada Lembaga Keuangan Syari’ah Terhadap Kepuasan dan Loyalitas Nasabah di Bank Muamalat Indonesia Kantor Cabang Yogyakarta - Annas Syams Rizal Fahmi Fahmi (Faculty of Economics and Management, 2019)
Customer loyalty is a very important factor in the world of financial institutions, because loyalty is largely determined by customer satisfaction itself, so customer satisfaction greatly affects customer loyalty. In this case the researcher will examine the Financial Institution in terms of services provided to customers, whether the service has an influence on customer satisfaction and loyalty tofinancial institutions. Researchers are interested in Bank Muamalat Indonesia as the originator of Islamic banks in Indonesia, which can keep the economic system in Indonesia stable during the monetary crisis. In this case as a Sharia Bank, financial institution services provided should be the maximum service in accordance with Islamic values, this is one of the factors researchers to analyze,whether the services provided by banks can provide satisfaction to consumers, and whether bank customers muamalat Indonesia already feel satisfied or not. Then to make it easier to analyze the data, researcher used the SPSS measuring instrument, using instruments from the Likert scale, validity test, reliability test, classic assumption test. In analyzing the data the authors useprimary data and secondary data, namely by questionnaires, and interviews and company documents as secondary data. Then it will be tested using multiple linear regression testing, so that it will come out the data t arithmetic, t table, f arithmetic, and f table.Based on the t test the Service variable influences Customer Satisfaction at Bank Muamalat Indonesia Yogyakarta Branch Office, which can be shown by t count greater than table (1,981> 1,290). And based on the t test shows that t count is greater than t table (2.188> 1,290), meaning that the service variable has a significant positive effect on customer loyalty variables. From the results ofresearch that has been measured with this SPSS tool it is found that service has a significant effect on customer satisfaction and loyalty.